Sosialisasi Peningkatan Derajat Sehat Melalui Asupan Gizi dalam Pencegahan Stunting di Lingkungan Pondok Pesantren Asshulahaa Serta MI Asshulahaa Cieurih - Afif, Ucu Muhammad; Hidayat, Cucu; Rahmat, Agus Arief; Aang Rohyana (Edutech Journals, 2024)
Santri as the main driving force of pesantren has great potential to be improved. This includes housewives who are still unfamiliar with caring for their children. By changing behavior and adding awareness, it is expected to have the power to improve health. Stunting is a public health problem that must get serious attention. The problem that occurs is that partners lack awareness related to healthy degrees and good nutritional intake, stunting data according to Opendata data in the partner environment recorded 78 people in 2022. The purpose of this article is to provide education in the form of socialization, especially improving health status through nutritional intake as an effort to prevent stunting. This community service concentrates on the environment around the Asshulahaa Islamic Boarding School and guardians of Madrasah Ibtidaiyah (MI) Asshulahaa Cieurih students. The methods in implementing this service include: 1) The socialization stage, the audience stage and the stage of providing nutritious food assistance. The results in this service are The material provision activities went well, as evidenced by the enthusiasm of the participants during the discussion session where the participants asked questions and learned activities related to nutritious food in an effort to prevent stunting.